Hypervirulent Mycobacterium tuberculosis strain triggers necrotic lung pathology associated with enhanced recruitment of neutrophils in resistant C57BL/6 mice - Almeida, Fabrício M.; Ventura, Thatiana L. B.; Amaral, Eduardo P.; Ribeiro, Simone C. M.; Calixto, Sanderson D.; Manhães, Marcelle R.; Rezende, Andreza L.; Souzal, Giliane S.; de Carvalho, Igor S.; Silva, Elisangela C.; Silva, Juliana Azevedo da; Carvalho, Eulógio C. Q.; et al. (PloS one, 2017)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis (Mtb) that in most cases induces irreversible necrosis of lung tissue as a result of excessive inflammatory reactions. The murine model of TB in resistant C57BL/6 mice infected with reference Mtb strains is widely used in TB studies; however, these mice do not show a necrotic pathology, which restricts their use in studies of irreversible tissue damage. Recently, we demonstrated that necrotic lung lesions could be induced in the C57BL/6 mice by highly virulent Mtb strains belonging to the modern Beijing sublineage. However, the pathogenic mechanisms leading to necrosis in this model were not elucidated. In this study, we investigated the dynamics of lung lesions in mice infected with highly virulent Beijing Mtb strain M299, compared with those infected with laboratory Mtb strain H37Rv. The data demonstrate that necrotic lung lesions in mice infected by the strain M299 were associated with enhanced recruitment of myeloid cells, especially neutrophils, and increased levels of proinflammatory cytokines, consistent with exacerbated inflammation. High levels of IFN-γ production contributed to the control of bacterial growth. Further progression to chronic disease was associated with a reduction in the levels of inflammatory mediators in the lungs, the accumulation of foamy macrophages and partial healing of the necrotic tissue by fibrosis. At a late stage of disease, degradation of foamy cells resulted in the liberation of accumulated lipids and persisting bacilli and further activation of inflammation, which promoted lung consolidation. Overall, our studies show that C57BL/6 mice infected with highly virulent Mtb strain may serve as a TB model reproducing an exacerbated inflammatory response in a resistant host to hypervirulent mycobacteria, leading to irreversible necrotic lung lesions.